Karakter Morfologis Kultivar Padi Ketan Lokal Ponorogo - Hamawi, Mahmudah; Setyaningrum, Haris; Etica, Use (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2019)
Morphological characters are basic characters to identify rice cultivars. The information of glutinous rice cultivars in Ponorogo is still very limited, therefore the exploration and characterization of the local cultivar are needed. The research aimed to explore and identify local cultivars based on morphological characters of plant, grain, and milled rice. The research was conducted on March-October 2018 at elevens subdistricts in Ponorogo. There were eleven cultivars have been collected and characterized, namely five white glutinous rice cultivars (Latisa, Tawon, Semok, Pelem, Genjah), three red glutinous rice cultivars (Garingan, Merah Pendek, Jowo), and three black glutinous rice cultivars (Wilis, Gundik, dan Gontor Bulu). The eleven cultivars were varied on plant height, panicle length, flowering time, number of tillers, grain size and shape, and the color of aleurone. The analysis of diversity and similarity on characters showed that all cultivars could be classified into four different groups. The first group was Latisa (Gontor Bulu), the second was Tawon group (Pelem), third was Genjah group (Garingan, Merah Pendek and Jowo), and the fourth was Wilis group (Gundik). Keywords: aleurone , diversity, exploration, rice grain, similarity